Potential of a web system to support learning in the COVID-19 pandemic using effective methods for knowledge construction (Research, Society and Development, 2021)
This work presents the potential of a web system that implements an interface between the teacher and the student through remote teaching, to be used as a complement for learning in this period of the COVID-19 pandemic. Where it enables both a knowledge interface, both for the student and for the teacher. In which the teacher makes available material that is really in their domain and competent to what they want to mediate knowledge for the student, preventing them from accessing material divergent from what will be placed in situations that should expose the knowledge and that the student can abstract from this content knowledge that will be consolidated in your memory. The research has an exploratory-descriptive nature. In this context, the objective of this study was to develop a web system that helps the student in retaining knowledge and in the security of applying their skills in hypotheses that the impediment. The algorithm of the Effective Exponential Memory Method in Binary Base - MMEEBB was used in the system, which allows the individual to learn a content and retain it in their memory, where the MMEEBB creates intervals of learning reinforcements that must be followed to maintain consolidated knowledge.